Investigation of the surface layer of wheel steel by indentation method - Kanaev, A.; Moldakhmetova, A.; Kossanova, I. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article considers methods of measurement of microhardness and modulus of elasticity of plasma hardened wheel steel by kinetic indentation method. It provides features of measurement of microhardness, modulus of hardness, elastic recovery, influencing on wear resistance of surface layers of steel. Measurement of these characteristics of material allows estimating and choosing optimum technology of surface modification by surface plasma hardening. It is confirmed that objectivity of determination of microhardness, modulus of elasticity, elastic recovery and flow stress depends on strict observance of imprint depth requirements depending on thickness of hardened layer. It is noted that in spite of the increased amount of factual information, obtained by indentation method, the physical substantiation of hardness micro-mechanisms remains poorly understood, which necessitates substantiation of physical representations of the nature of hardness of metallic materials. It is established that the measurement of microhardness, elastic modulus and elastic recovery by the kinetic indentation method is expedient to use for certification of the surface layer of plasma-hardened wheel steel according to the parameters of physical and mechanical characteristics.